Does Gold Act as a Hedge or a Safe Haven against Equity and Currency in Asia? - Aftab, Muhammad; Shah, Syed Zulfiqar Ali; Ismail, Izlin (SAGE Publications, 2019)
In recent years, uncertainty in financial markets has stimulated the need to explore alternative avenues for safeguarding wealth and managing risk. In this strand of research, gold has been particularly important due to its potential to mitigate risk and preserve wealth. This study investigates gold behaviour against equities and currencies in three regions across Asia. We follow Engle’s (2002) dynamic conditional correlation-multivariate generalized autoregressive conditional heteroscedasticity (DCC-MGARCH) model to test the gold link with equity and currency markets. We use a weekly series of exchange rate (national currency/the US dollar), equity and gold prices in national currency over the weekly period, 1995–2013. The sample consists of 12 countries covering East Asia, South Asia and Southeast Asia. Findings suggest that gold is just a diversifier against stocks in the Asian economies except in Korea, Singapore and Thailand. However, gold acts as a hedge and safe haven against Asian currencies—except China and Hong Kong—thus still preserving its monetary role.